Efektivitas Pelatihan Motivasi untuk Meningkatkan Motivasi Kerja Pekerja Outsourcing Sebagai Cleaning Service di UIN Imam Bonjol Padang - Winbaktianur, Winbaktianur; Putri, Nadya Ulfa Risya (Universitas Islam Negeri Raden Intan Lampung, 2017)
This article aims to determine the work motivation of outsourced workers before being given motivation training, knowing the work motivation of outsourced workers after being given motivation training. Then know whether there is an influence of motivation training to improve work motivation and know the smoothness of motivation training. The research method used is a pure experimental method, with pretest-posttest control group design research design. The subjects of the research are outsourced workers as cleaning service in UIN Imam Bonjol Padang totaling 30 people. Subjects were selected based on randomization measured using a work motivation scale, which was divided into two groups: the experimental group and the control group. Each group has 15 people. The experimental group was given treatment in the form of motivation training, while the control group did not. Based on the pretest results, the experimental group and the control group showed moderate work motivation. In the posttest results, the experimental group experienced improvement after treatment. While the control group that was not given treatment there was no increase, even the decrease of work motivation. The result of the research proves that the giving of motivation training has an effect on the increase of work motivation to the outsourced workers as cleaning service in UIN Imam Bonjol Padang. The training implementation questionnaire proved that motivational training was going well for the participants.